Microhabitat hydraulics predict algae growth in running systems - Cardoso-Leite, Ricardo; Guillermo-Ferreira, Rhainer; Novaes, Marcos Carneiro; Tonetto, Aurelio Fajar [UNESP] (Int Centre Ecology, Polish Acad Sciences, 2015)
The properties of surface roughness have been considered an important factor in algal growth. The most relevant finding is that rougher surfaces supports higher algal accumulation. However, the stimulatory effects of roughness have not been tested so far. Thus, here we carried out an experiment using an increasing level of roughness in two different flow conditions. Hence, we investigated the roughness stimulatory threshold for algae growth under different flow conditions, in order to assess the effect of hydraulic dynamics. In the slower flow, the stimulatory threshold did not occurred (high algal coverage in all roughness levels), while in the faster one it could be observed (algal coverage varies among roughness levels). The drag force in slower flow flume was lower than in faster flume. The low values of drag force may have reduced the effects of roughness, which was highlighted in the fast flow flume. Therefore, we suggest that hydraulic dynamics can regulate the roughness stimulatory threshold mechanisms and the peak of algal accumulation is directly dependent of these conditions. (C) 2014 European Regional Centre for Ecohydrology of Polish Academy of Sciences. Published by Elsevier Urban & Partner Sp. z o.o. All rights reserved.